Nature’s contribution to people provided by pastoral systems across European, African, and Middle East Mediterranean countries: trends, approaches and gaps - Graeme Dean; Matteo Francioni; Marco Toderi; Feliu López-i-Gelats; Laura Trozzo; Marta G. Rivera-Ferre; Antonello Franca; Giovanni M. Altana; Maria Karatassiou; Zoi M. Parissi; Eleni M. Abraham; Athanasios Ragkos; et al. (Regional Environmental Change, 2024)
Mediterranean pastoral systems are providers of a wide array of Nature’s Contribution to People (NCP). They are ‘complex systems’ characterized by limited resources and socio-economic dynamics currently threatened by climate and social changes. Despite a growing number of scientific articles dealing with NCP, there is a high risk that the existing literature has left out the complexity of such systems. In the light of ongoing social, economic, and climatic changes in the Mediterranean basin, neglecting the complexity of pastoral systems can lead to significant research biases, missing the priorities affecting the stability and continuity of such systems. A combination of frameworks of analysis provided by the Millennium Ecosystem Assessment and by the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services was applied to understand if and to what extent the complexity of Mediterranean pastoral systems has been considered in the available literature. Most of the 126 papers report studies conducted in the European Union zone (102 papers), with the majority in Spain (50). Fewer studies have been conducted in the Middle East (15 papers) and Africa zones (9 papers). Despite results confirming the importance of pastoral systems as providers of NCP, most of the eligible papers focused on regulating NCP. A lack of a multisectoral approach and integration of knowledge suggests that the complexity of Mediterranean pastoral systems has been overlooked by researchers. The creation of ‘hybrid knowledge’ bridging the expertise of different stakeholders could be the key ingredient to properly address the complexity of Mediterranean pastoral systems.

Effect of wood gasification biochar on soil physicochemical properties and enzyme activities, and on crop yield in a wheat-production system with sub-alkaline soil - Nora Baldoni; Matteo Francioni; Laura Trozzo; Marco Toderi; Flavio Fornasier; Paride D'Ottavio; Giuseppe Corti; Stefania Cocco (Biomass and Bioenergy, 2023)

Sustainable Catchment Managing in a Climate Changing World: New Integrative Modalities for Connecting Policy Makers, Scientists and Other Stakeholders - Ray Ison; Kevin Collins; John Colvin; Janice Jiggins; Pier Paolo Roggero; Giovanna Seddaiu; Patrick Steyaert; Marco Toderi; Chiara Zanolla (Water Resources Management, 2011)